2021
DOI: 10.1136/bmjopen-2020-042871
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impacts of the COVID-19 pandemic on family mental health in Canada: findings from a national cross-sectional study

Abstract: ObjectivesIn the first wave of the COVID-19 pandemic, social isolation, school/child care closures and employment instability have created unprecedented conditions for families raising children at home. This study describes the mental health impacts of the COVID-19 pandemic on families with children in Canada.Design, setting and participantsThis descriptive study used a nationally representative, cross-sectional survey of adults living in Canada (n=3000) to examine the mental health impacts of the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
306
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(383 citation statements)
references
References 40 publications
(31 reference statements)
26
306
2
5
Order By: Relevance
“…Also, the existence of domestic conflicts negatively affected the emotional, psychological and social well-being of our participants. This is also in line with previous studies during COVID-19 pandemic indicating that domestic conflicts during the pandemic (such as have resulted in deteriorated mental health [71].…”
Section: Discussionsupporting
confidence: 93%
“…Also, the existence of domestic conflicts negatively affected the emotional, psychological and social well-being of our participants. This is also in line with previous studies during COVID-19 pandemic indicating that domestic conflicts during the pandemic (such as have resulted in deteriorated mental health [71].…”
Section: Discussionsupporting
confidence: 93%
“…In May 2020, about half of families reported that keeping children on a daily routine was effective in managing parenting difficulties, and over time, this percentage increased, suggesting this strategy was working for more families. A previous study also found that maintaining family routines helped children to cope with COVID-19-related stress (27). During this time of unpredictability in a rapidly changing environment, it can be difficult for families to keep a consistent daily routine.…”
Section: Discussionmentioning
confidence: 91%
“…Around the height of government closures and stay-athome orders (May 2020), one-in-five parents reported high stress, while three-in-four parents reported increased parentingspecific stress. Multiple other studies have found that high stress was a common initial reaction to this pandemic (26)(27)(28)(29)(30) and that parents are experiencing more stress than non-parents (17). These previous data were mostly collected in April/May 2020; therefore, the unique aspect of this study includes the longitudinal data across two timepoints during COVID-19 (May and September 2020), as the pandemic progressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher stress levels associated with lockdown measures were observed in some groups, such as women [185][186][187] (particularly pregnant women 188,189 ), single/divorced adults 81 , older people (particularly with pre-existing mental health conditions 175,190 ), parents with young children 191 , university students and young adults [192][193][194] , workers 195 , those self-medicating 196 , the economically deprived 143 , those with pre-existing depression 197 , bipolar disorders 198 , and other chronic medical conditions 139,189,[199][200][201] . A large study of 56,679 participants in China found that quarantine had a profound effect on the mental health of specific vulnerable groups, including those with pre-existing mental disorders, chronic physical diseases, frontline workers, and those living in the most affected areas 202 .…”
Section: Stressmentioning
confidence: 99%